Valorization of raw papaya (Carica papaya) and citrus peels for development of antimicrobial and biodegradable edible film - Prathamesh Pawle; Surabhi Pandey; Arvind Kumar; Aparna Agarwal; Abhishek Dutt Tripathi; Mohd Saeed; Safia Obaidur Rab; Dipendra Kumar Mahato; Pradeep Kumar; Madhu Kamle (Food Chemistry: X)
Most of the food packaging materials used in the market are petroleum-based plastics; such materials are neither biodegradable nor environmentally friendly and require years to decompose. To overcome these problems, biodegradable and edible materials are encouraged to be used because such materials degrade quickly due to the actions of bacteria, fungi, and other environmental effects. The present study examined that starch can be effectively used as raw material to develop biodegradable, edible films. In this regard, Raw papaya and Citrus Peel were chosen to make biodegradable plastic film blended with corn starch. Raw papaya powder was combined with citrus peel powder for the development of film in treatments of T1, T2, T3, T4 and T5. RPP and CPP blend with Corn starch (CS) to maximize the film-forming properties and characteristics. The films were subjected to various parameter analysis like thickness, optical properties and barrier properties. As per the results, T3 was an optimized film, as it had minimum thickness (0.26 ± 0.01), high tensile strength (5.79 ± 0.12), elongation at break of 11.92 ± 0.03, High transparency (1.42 ± 0.06), and high degradation temperature. From the results, it is inferred that the prepared films are ideally suitable for food packaging and their production on a larger scale can considerably cut down the plastic wastage.